Imagens da metrópole no cinema brasileiro - Alencar, Marlivan Moraes de (2008)
This thesis argues the images of the metropolis constructed by the contemporary Brazilian cinema. The analysis foresees at least three elements that are on the basis of this cinema: (1) the fi lm as an intellectual experience and mediation; (2) the necessity to consider the fi lm form as a fundamental element in the construction of this mediation; and (3) the city as an environment mobilized for the interaction between the people and the modifi ed space. For the present study it was selected four feature fi lm fi ctions, directed by young movie makers from different Brazilian states: O Invasor (2001), of Beto Brant, O homem que copiava (Rio Grande do Sul, 2002), of Jorge Furtado; Amarelo Manga (Pernambuco, 2002), of Cláudio Assis;; and, O outro lado da rua (Rio de Janeiro, 2004), directed by Marcos Bernstein. All of them deal with the comprehension of the images as something capable to set the imaginary, and, to assume with the motivational questionings of this thesis the inquiries on what and how these movies are thinking the life in metropolis. The analysis is structured from the relationship between subject/personage and the urban environment, considered as force lines to defi ne conceptual cities identifi ed by those relationships. The adopted theoretical position assumes a multidisciplinary character as a necessary condition for the analytical process, connected to areas such as Anthropology, Sociology, Philosophy and Cinema Theory, among others. The thesis is divided in three chapters: the fi rst one is a discussion that considers O invasor (2001) and O homem que copiava (2002) as similar movies since they have a structural similarity, which is the point of view of the metropolis as a place still under construction, a process of transformation between the virtual and the reality; and for this reason the chapter is titled Virtual city . The second chapter titled The city to drift (adrift) approaches the fi lm feature from Pernambuco as a movie composed by floating images that try to prove the thesis of its director about the misery in man s life. Finally, the third chapter, titled The body-city , considers that the movie of Bernstein, through a classic decoupage, approaches its protagonist to the metropolis in order to con- fi gure among them an almost indissociated relationship